Anaemia In Preschool Children:its Correlation With Pica - Kaur, Sukhdeep; Pal Singh, Kunwar (Journal of Nepal Paediatric Society, 2022)
Introduction: According to the third National Family Health Survey, 79% of Indian children are anaemic. Pica is characterized by the persistent ingestion of non-nutritive substances such as plaster, charcoal, chalk, and earth for at least one month in a manner that is inappropriate for their developmental level. We investigated the correlation between pica behaviour and anaemia in preschool children. Methods: In total, 103 children of ages six to 48 months attending the OPD were randomly included in this study for six months; they presented with clinical features of anaemia. Complete blood count and peripheral blood film examination were carried out. The children were assessed clinically for signs and symptoms of anaemia. History of ingestion of clay, sand, chalk, wall paints etc was asked from the parents. Results: Most of the children (90.3%) had microcytic hypochromic anaemia with a mean haemoglobin value of 8.82 g / dl. The mean age was 18 months, and boys slightly outnumbered girls. In total, 57.3% of children had a positive history of pica, and all of them were found to be anaemic. However, no significant statistical correlation was observed between anaemia and history of pica. Conclusions: All children with history of pica were anaemic and the most common type of anaemia was microcytic hypochromic. Although no significant statistical correlation was observed between and history of pica, it is very important for the clinicians to be cautious of this common condition and evaluate for anaemia